Demand‐ and Supply‐Side Agglomerations: Distinguishing between Fundamentally Different Manifestations of Geographic Concentration - McCann, Brian T.; Folta, Timothy B. (Journal of Management Studies, 2009)
abstract Agglomeration research investigates the benefits that firms receive from locating in close geographic proximity. Despite a substantial surge in interest in this topic over the past 20 years, a lack of distinction among unique manifestations of spatial concentrations of similar firms threatens continuing progress in this stream of research. We argue that agglomerations of related firms that draw benefits from the supply‐related externalities of increased access to specialized labour, specialized inputs, and knowledge spillovers are fundamentally different from those that draw benefits from heightened demand realized through reduction in consumer search costs. Extending agglomeration theory, we explicate the differences between these distinct phenomena, discuss how the nature of key theoretical relationships varies across these agglomeration types, and demonstrate significant implications for research. We discuss how the differences affect a host of theoretical relationships and empirical research decisions.